NSUN2-mediated RNA 5-methylcytosine promotes esophageal squamous cell carcinoma progression via LIN28B-dependent GRB2 mRNA stabilization - Su, Jiachun; Wu, Guandi; Ye, Ying; Zhang, Jialiang; Zeng, Lingxing; Huang, Xudong; Zheng, Yanfen; Bai, Ruihong; Zhuang, Lisha; Li, Mei; Pan, Ling; Deng, Junge; et al. (Oncogene, 2021)
5-Methylcytosine (m 5 C) is a posttranscriptional RNA modification participating in many critical bioprocesses, but its functions in human cancer remain unclear. Here, by detecting the transcriptome-wide m 5 C profiling in esophageal squamous cell carcinoma (ESCC), we showed increased m 5 C methylation in ESCC tumors due to the overexpressed m 5 C methyltransferase NSUN2. Aberrant expression of NSUN2 was positively regulated by E2F Transcription Factor 1 (E2F1). High NSUN2 levels predicted poor survival of ESCC patients. Moreover, silencing NSUN2 suppressed ESCC tumorigenesis and progression in Nsun2 knockout mouse models. Mechanistically, NSUN2 induced m 5 C modification of growth factor receptor-bound protein 2 ( GRB2 ) and stabilized its mRNA, which was mediated by a novel m 5 C mediator, protein lin-28 homolog B (LIN28B). Elevated GRB2 levels increased the activation of PI3K/AKT and ERK/MAPK signalling. These results demonstrate that NSUN2 enhances the initiation and progression of ESCC via m 5 C-LIN28B dependent stabilization of GRB2 transcript, providing a promising epitranscriptomic-targeted therapeutic strategy for ESCC.